Nomenclatural notes in miscellaneous species of Acianthera (Pleurothallidinae, Orchidaceae) - Brito, A. L. V. Toscano De; Smidt, Eric De Camargo (Phytotaxa, 2023)
A new combination, Acianthera kautskyi, is proposed. Acianthera sudae is proposed as a new synonym of the former. Acianthera crinita has been shown to be distinct from A. kautskyi. We provide in this article the taxonomic comments, illustrations, and images on these two taxa.